2022
DOI: 10.48550/arxiv.2204.07425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding Hall blockers by matrix scaling

Abstract: For a given nonnegative matrix A = (A ij ), the matrix scaling problem asks whether A can be scaled to a doubly stochastic matrix XAY for some positive diagonal matrices X, Y . The Sinkhorn algorithm is a simple iterative algorithm, which repeats row-normalization A ij ← A ij / j A ij and column-normalization A ij ← A ij / i A ij alternatively. By this algorithm, A converges to a doubly stochastic matrix in limit if and only if the bipartite graph associated with A has a perfect matching. This property can dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[Aas14] showed that the accumulation points exhibit a block diagonal structure which can be characterized combinatorially. Recently, Hayashi and Hirai [HH22] proved that one can obtain a Hall blocker (dual certificate showing that a given matrix has no scaling) by the Sinkhorn iteration.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[Aas14] showed that the accumulation points exhibit a block diagonal structure which can be characterized combinatorially. Recently, Hayashi and Hirai [HH22] proved that one can obtain a Hall blocker (dual certificate showing that a given matrix has no scaling) by the Sinkhorn iteration.…”
Section: Related Workmentioning
confidence: 99%
“…The authors thank Nikhil Srivastava for references to eigendecomposition algorithms. The authors also thank Koyo Hayashi and Hiroshi Hirai for references [Aas14,GR13] and sharing a draft of [HH22].…”
Section: Acknowledgementsmentioning
confidence: 99%